Assessment of Response to Neoadjuvant Chemoradiotherapy by 18F-FDG PET/CT in Patients With Locally Advanced Esophagogastric Junction Adenocarcinoma. (January 2020) - Sánchez-Izquierdo, Nuria; Perlaza, Pilar; Pagès, Mario; Buxó, Elvira; Rios, José; Rubello, Domenico; Colletti, Patrick M.; Mayoral, Maria; Casanueva, Sebastian; Fernández-Esparrach, Gloria; Ginés, Angels; Fuster, David
Abstract : Purpose: The outcome of locally advanced adenocarcinoma of the esophagogastric junction (AEG) treated with preoperative chemoradiotherapy is heterogeneous, and favorable response to this treatment is a key factor in the patient's prognosis. The aim of this study was to evaluate 18 F-FDG PET/CT in assessing metabolic response in patients with AEG. Materials and Methods: This prospective study evaluated all consecutive patients with potentially operable locally advanced AEG who were candidates for neoadjuvant chemoradiotherapy. PET/CT and contrast-enhanced thoracoabdominal CT were performed at baseline and 2 weeks after completion of chemoradiotherapy for response evaluation. The response rate was assessed using Response Evaluation Criteria in Solid Tumors criteria for contrast-enhanced thoracoabdominal CT and Positron Emission Tomography Response Criteria in Solid Tumors criteria for PET/CT. The regression rate was assessed using a 5-grade histopathology scoring system of the surgically resected tumor. Metastatic lesions were confirmed by histopathology examination or imaging and clinical follow-up at 6 months. Results: A total of 40 cases were finally included in the study. Distant metastases were found in the baseline PET/CT in 6 of 40 cases (retroperitoneal [2] or mediastinal/hiliar [1] lymph nodes and liver [2] or bone [1] metastases) and were therefore excluded from surgery. Pathologic response correlated with the ΛSUVmax threshold of ⩽45% ( P = 0.033). CT response correlated well with both the baseline SUVmax ( P = 0.039) and the ΛSUVmax ( P = 0.001). Five-year survival curves for AEG correlated with the ΛSUVmax using a threshold of ⩽45% for both progression-free and overall survival. Conclusions: 18 F-FDG PET/CT is useful for diagnosing nonsuspected metastasis before neoadjuvancy in potentially operable AEG. The ΛSUV correlates with pathologic response and is a long-term independent prognostic factor of survival.